Rural education in Latin America: A historical study - Patricia de Souza Machado Gregorio; Gledson Vigiano Bianconi (Universidade Federal do Norte do Tocantins, 2023)
Rural Education (RE) is being conceived as a pedagogical proposal specific to the rural population, as it considers that this audience has distinct educational needs and lifestyle habits from those living in urban environments. In this article we presented the results of bibliographical Research aimed at the historical survey of teaching proposals in this modality within Latin America, adopting as a sample cut the histories of Argentina, Brazil, Cuba, and Mexico. Our results demonstrate that Latin American experiences are influenced by the ideological inclination of their governments and that educational projects achieved better results when they obtained greater popular participation, from their conception to the execution of their proposals. This demonstrates that RE is a reflection of a Pedagogical Project that achieves higher levels of efficiency when built in a democratic, with the target audience involved in its construction.